Assessing the impacts of collection-delivery points to individual's activity-travel patterns: A greener last mile alternative?. (January 2019) - Liu, Chengxi; Wang, Qian; Susilo, Yusak O.
Highlights: Travel pattern of trips to/from collection-delivery points (CDPs) are studied. Disaggregated collection-delivery trip demand model is developed. Substantial VKT reduction can be achieved from relocating CDPs to suburban/rural areas. Abstract: The transport impacts of collection-delivery points (CDPs), as an alternative to home delivery, are rarely studied. As e-shopping becomes increasingly popular, trips to collect deliveries at CDP, especially by car travel, may generate a considerable amount of external effects, such as emissions. Therefore, this paper analysed the "picking up/leaving goods" trips selected from the Swedish National Travel Survey and jointly modelled the individuals' mode choice and trip chaining decisions using a panel cross-nested logit model. The roles of trip chain characteristics, individual socio-demographics and land use characteristics on each trip chain and mode choice combination are investigated. The results indicate observed and unobserved heterogeneities of trip chaining and mode choice decisions among populations. Young adults living with partners/spouses, single adults with children and partnered adults with children have the preference of using cars in collection-delivery trips compared to other life-cycle groups. A sensitivity analysis is carried out to estimate the effect of distance to CDPs on vehicle kilometres travelled. The calibrated model is used to estimate the VKT of collection-delivery trips in the greater Stockholm area. The results indicate a 22.5% reduction of VKT from collection-delivery trips by relocating 5% CDPs from urban areas to suburban and rural areas.